Enhanced Bone Cancer Diagnosis through Deep Learning on Medical Imagery - M. Venkata Ramana; P.N. Jyothi; S.Anuradha; G. Lakshmeeswari (International Journal of Computational and Experimental Science and Engineering, 2025)
Bone cancer, especially osteosarcoma, is an aggressive tumor with a highly complex histopathologic appearance that imposes considerable diagnostic difficulties. Although practical and efficient, traditional diagnostic methods and current deep learning models have a class imbalance, fused pixel intensity distributions, and tumor tissue heterogeneity that hinder diagnostic efficiency. These problems emphasize the demand of more sophisticated frameworks that specifically address the distinct properties of bone cancer histopathology images. To overcome these shortcomings, in this study proposes a deep learning framework, IBCDNet, to alleviate these limitations. Inspired by cutting-edge improvements in architecture (e.g., like attention, residual connections, and the proposed Intelligent Learning-Based Bone Cancer Detection (ILB-BCD) algorithm), the proposed framework combines different features from both public and private datasets in an efficient way. This allows for strong feature extraction, better learning from imbalanced data, and thus precise classification. The proposed model obtains state-of-the-art results of 98.39% on the Osteosarcoma Tumor Assessment Dataset, outperforming powerful baseline models like ResNet50, DenseNet121, and InceptionV3. This further affirms its diagnostic robustness with the respective precision (97.8%), recall (98.1%), and F1-score (98.0%) which shows a remarkable improvement We present a cost-effective framework for scalable real-world clinical applications to assist pathologists for early detection and accurate diagnosis of bone cancer. Those important gaps identified and addressed by this research contribute to the progress towards AI-driven healthcare and towards the global goals of precision medicine and enhanced patient outcomes.